Implementasi Kebijakan Pemerataan Pendidikan dalam Mengatasi Ketimpangan Akses di Daerah Terpencil - Vilanti, Friska Aqilah; Harli Hanapi, Muhammad; Viola, Mayshel Adinda; Pratama, Linardo (UPT Perpustakaan Universitas Jambi, 2026)
Unequal access to education remains a major issue in Indonesia, particularly in remote areas that face shortages of facilities, infrastructure, and teaching staff. This study aims to analyze the implementation of educational equity policies, along with the supporting factors, obstacles, and improvement strategies. The research method employed is a literature study by examining relevant literature, regulations, and previous research findings. The results indicate that educational equity policies have been pursued through various initiatives such as the School Operational Assistance (BOS) program, improvement of educational infrastructure, and the deployment of teachers to underdeveloped, frontier, and outermost (3T) regions. However, field implementation still encounters challenges, including limited basic facilities, uneven distribution of teachers, low community support, and difficult geographical conditions. Key elements supporting successful policy implementation include adequate infrastructure provision, development of teacher competencies, and active involvement of local governments. Meanwhile, the main barriers arise from poor infrastructure, limited school capacity, and inconsistent policy application. This study concludes that equitable access to education will be achieved if the government strengthens collaboration between central and local authorities, enhances support for teachers in remote areas, and optimizes the fair allocation of educational resources.